Electrifying Nigeria: The impact of rural access to electricity on kids' schooling - Enrico Nano (Graduate Institute of International and Development Studies, 2022)
As of 2020, 770 million people still lack access to electricity worldwide and 10% of this population is in Nigeria. Nevertheless, the country has received so far little attention in this respect from the academic community. The economic literature also does not generally agree on the impact of access to electricity on education outcomes, despite being the object of several programmes and policies, and one of the key SDGs of the 2030 Agenda. This paper aims at filling these gaps in the literature by providing a medium-term analysis of the effect of village-level electricity access on kids' schooling in rural Nigeria. It also contributes to the methodological debate using a novel instrument in this context, namely the frequency of lightning strikes in the area surrounding households. The results show that electricity access leads to an increase in school enrolment and a decrease in the grade-for-age (GFA) gap, a measure of educational performance. The paper also discusses some of the mechanisms that can lead to the observed findings, their robustness and heterogeneity, as well as the role of the quality of electricity received.
Keywords: O12; O13; I25; Q48; 330; Energy Access; Rural Electrification; Education; School Enrolment; Nigeria